Study on the Existence of the Shadow Terminal on the Pasir Hayam Terminal Service - Deden Irawan; Sri Hendarto; Didin Kusdian (Jurnal Impresi Indonesia, 2024)
Many people are interested in using the shadow terminal area on Jalan Raya Cibeber as a place to wait for public transportation and an interaction point between modes and routes. The purpose of this study is to evaluate the existence of shadow terminals around Pasir Hayam Terminal, focusing on the factors that influence passenger preferences in choosing shadow terminals compared to official terminals.  This research method uses a quantitative approach, where Importance Performance Analysis (IPA) is used to evaluate public transportation users' satisfaction with the performance of shadow terminals and main terminals. In addition, the SWOT Analysis Method is used as a tool to help structure the problem, especially in analyzing the strategic environment, which consists of two aspects, namely the internal and external environment. The results of calculations and analysis using the IPA method show that comfort and convenience are the main factors that influence passenger preferences in choosing the Shadow Terminal. Another significant factor is the availability of clean and complete dining and toilet facilities.  Through SWOT analysis, Pasir Hayam Terminal is in quadrant 2 which indicates a diversification strategy. In this strategy, the focus will be on optimizing the strengths of the terminal, improving existing weaknesses, taking advantage of open opportunities, and overcoming threats that may be faced. In addition, this strategy includes efforts to increase the advantages of Pasir Hayam Terminal over Terminal Bayangan and utilize the potential of Terminal Bayangan as a strength.